Porous Titanium-6 Aluminum-4 Vanadium Cage Has Better Osseointegration and Less Micromotion Than a Poly-Ether-Ether-Ketone Cage in Sheep Vertebral Fusion - Wu, Su-Hua; Li, Yi; Zhang, Yong-Quan; Li, Xiao-Kang; Yuan, Chao-Fan; Hao, Yu-Lin; Zhang, Zhi-Yong; Guo, Zheng (Artificial organs, 2013)
Interbody fusion cages made of poly‐ether‐ether‐ketone (PEEK) have been widely used in clinics for spinal disorders treatment; however, they do not integrate well with surrounding bone tissue. Ti‐6Al‐4V (Ti) has demonstrated greater osteoconductivity than PEEK, but the traditional Ti cage is generally limited by its much greater elastic modulus (110 GPa) than natural bone (0.05–30 GPa). In this study, we developed a porous Ti cage using electron beam melting (EBM) technique to reduce its elastic modulus and compared its spinal fusion efficacy with a PEEK cage in a preclinical sheep anterior cervical fusion model. A porous Ti cage possesses a fully interconnected porous structure (porosity: 68 ± 5.3%; pore size: 710 ± 42 μm) and a similar Young's modulus as natural bone (2.5 ± 0.2 GPa). When implanted in vivo, the porous Ti cage promoted fast bone ingrowth, achieving similar bone volume fraction at 6 months as the PEEK cage without autograft transplantation. Moreover, it promoted better osteointegration with higher degree (2‐10x) of bone‐material binding, demonstrated by histomorphometrical analysis, and significantly higher mechanical stability (P < 0.01), shown by biomechanical testing. The porous Ti cage fabricated by EBM could achieve fast bone ingrowth. In addition, it had better osseointegration and superior mechanical stability than the conventional PEEK cage, demonstrating great potential for clinical application.